Effectiveness of teacher selected strategies on students’ academic performance in mathematics, A case of form three students. (International Journal of Scientific Research and Management (IJSRM), 2019)
Mathematics is a compulsory subject to all students. It is regarded as a career subject since anything students do after high school revolves around mathematics. Teachers of mathematics always strive to improve students’ performance in mathematics. They always make sure that they complete the syllabus to give students a chance to do better in mathematics. Despite the importance of mathematics, most students in many schools still fail mathematics Examinations. The performance over the years has been persistently very poor. The purpose of this study was to find out which of the strategies of learning mathematics improves students achievement in mathematics; individualization for Mastery approach (IMA) or completing the syllabus (CSA).This entailed the use of the two approaches in the learning of Vectors 11; a form three mathematics topic. This study investigated the relationship between the achievement of students where teachers of mathematics used Individualization for Mastery approach (IMA) and those ones where the teachers worked hard to complete the syllabus. The theoretical framework which guided this study was social constructivism theory. The study adopted a pre-test post-test non-equivalent group design. The target population for this study was all the form three students in 39 secondary schools in Mumias sub-county. Stratified random sampling was used to select schools that took part in the study. The strata were Boys’ schools, Girls’ schools and co-educational schools. From girls’ and co- education schools, the researcher randomly selected three schools from each out of 10 and 26 schools respectively, while from boys’ schools; two schools were selected using saturation sampling giving a total of eight (8) schools that participated in the study. One stream selected randomly from each sampled school took party in the study. Experimental group had a total of 126 students while the Control group had 130 students. The Control group used completing the syllabus approach (CSA) while the Experimental group used Individualization for Mastery (IMA) approach. Each group (CSA and IMA) comprised of four schools selected randomly from the eight schools. The students’ Achievement test was used to collect data. The instrument was developed basing on the objectives and given to the experts in Mathematics Education to validate. To determine the reliability of the instrument, Split half technique was employed since it involves only one testing session and it eliminates chance error. Data was analyzed using both descriptive and inferential statistics. Results indicate that there is a significant difference in achievement between students who used Individualization for Mastery (IMA) approach and those who used completing the syllabus (CSA) strategy in favor of the (IMA) group.